2023
DOI: 10.1038/s41467-023-36290-w
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of ribosome profiling datasets reveals a function of rocaglamide A in perturbing the dynamics of translation elongation via eIF4A

Abstract: The quickly accumulating ribosome profiling data is an insightful resource for studying the critical details of translation regulation under various biological contexts. Rocaglamide A (RocA), an antitumor heterotricyclic natural compound, has been shown to inhibit translation initiation of a large group of mRNA species by clamping eIF4A onto poly-purine motifs in the 5′ UTRs. However, reanalysis of previous ribosome profiling datasets reveals an unexpected shift of the ribosome occupancy pattern, upon RocA tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 94 publications
(203 reference statements)
1
1
0
Order By: Relevance
“…S5F and S5G). Intriguingly, a large proportion of eIF4A1 binding was observed at the CDS (DMSO, 43±1%; ADR-treated, 39%, n = 2 each), in keeping with the recent observation that eIF4A1 may bind polypurine sequences in the CDS following RocA treatment 47 . Aggregate read distribution analysis of eIF4A1 binding within the 5′ UTRs themselves showed that under normal conditions (DMSO treatment) binding gradually increased in the 3′ direction toward the start codons, whereas following CMLD012824 treatment eIF4A1 binding was more pronounced at the 5′ end of 5′ UTRs (Fig.…”
Section: Cmld012824 Results In Promiscuous Eif4a1 Clamping Along Sens...supporting
confidence: 86%
See 1 more Smart Citation
“…S5F and S5G). Intriguingly, a large proportion of eIF4A1 binding was observed at the CDS (DMSO, 43±1%; ADR-treated, 39%, n = 2 each), in keeping with the recent observation that eIF4A1 may bind polypurine sequences in the CDS following RocA treatment 47 . Aggregate read distribution analysis of eIF4A1 binding within the 5′ UTRs themselves showed that under normal conditions (DMSO treatment) binding gradually increased in the 3′ direction toward the start codons, whereas following CMLD012824 treatment eIF4A1 binding was more pronounced at the 5′ end of 5′ UTRs (Fig.…”
Section: Cmld012824 Results In Promiscuous Eif4a1 Clamping Along Sens...supporting
confidence: 86%
“…Alternatively, the eIF4A1 clamping observed in the 3′ UTR regions may not contribute to decreases in translation, but rather may interfere with microRNA mediated inhibition, such as in the case of MYCN 56 . As has been suggested 47 , sustained clamping of eIF4A1 in the CDS may also modulate translation elongation, thereby accounting for the lack of correlation between 5′ UTR binding and translation efficiency. The significant degree of clamping we observed in the CDS and 3′ UTRs may also result in sequestration of eIF4A1, causing the cytotoxic effect of the ADR to be compounded by reducing the amount of free eIF4A1 that is available for translation of mRNAs without polypurine-rich motifs 30,57 .…”
Section: Discussionmentioning
confidence: 93%
“…These binding patterns were similar in CMLD012824-treated cells, suggesting that naive eIF4A1 cluster distributions along mRNAs are largely retained upon ADR-mediated clamping, with a modest increase observed when binding included 5′ UTRs or CDS together with the 3′ UTRs ( Figures S5F and S5G ). As in the control cells, a large proportion of eIF4A1 binding was observed at the CDS (DMSO, 43% ± 1%; ADR-treated, 39%), suggesting that the recent observation of eIF4A1 binding to polypurine sequences in the CDS following RocA treatment 47 may be due to naive eIF4A1 distribution on mRNAs. Aggregate read distribution analysis of eIF4A1 binding within the 5′ UTRs themselves showed that with DMSO-treatment, binding gradually increased in the 3′ direction toward the start codons, whereas following CMLD012824, eIF4A1 binding was more pronounced at the 5′ end of 5′ UTRs ( Figure 5D ), further demonstrating the sustained clamping ability of the compound.…”
Section: Resultsmentioning
confidence: 94%
“…However, as previously observed, 33 ADR-mediated clamping of eIF4A1 did not fully correlate with loss of translation efficiency, potentially due to the eIF4A1 clamping observed in the 3′ UTR regions, which may not contribute to decreases in translation but rather interfere with microRNA mediated inhibition, such as in the case of MYCN. 54 Binding of eIF4A1 in the CDS may also modulate translation elongation as described, 47 thereby accounting for the lack of correlation between 5′ UTR binding and translation efficiency. The significant degree of clamping we observed in the CDS and 3′ UTRs may also result in sequestration of eIF4A1, causing the cytotoxic effect of the ADR to be compounded by reducing the amount of total available eIF4A1.…”
Section: Discussionmentioning
confidence: 97%